The potential of artificial intelligence in vocational education research and development: A bibliometric study - Candra Dinata; Ima Luciany Milansari; Mochamad Bruri Triyono; Galeh Nur Indriatno Putra Pratama (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2025)
Artificial Intelligence (AI) is emerging as a revolutionary force that is changing how we interact and work and redefining the global education landscape, especially Vocational Education (VE). AI is an opportunity to develop learning research and good vocational Education. However, this opportunity has not been correctly utilized because not all educators can develop research and AI-based learning content well. This article reveals opportunities for current and future research development related to AI and vocational Education through bibliometric analysis. The database comes from Scopus, and 159 articles were analyzed from 2014 to 2023. Bibliometric analysis of documents, including author name, journal network, country, and keywords, is visualized using the VOSviewer program. The findings reveal three key insights: (1) research remains concentrated in vocational health, with limited exploration in other sectors such as engineering, tourism, and agriculture; (2) international collaboration is still weak, despite strong potential between countries with high and emerging publication rates; and (3) keyword clusters highlight Apprenticeship, Students, Artificial Intelligence, and Engineering Education as the main thematic areas. These insights form a roadmap for future research that emphasizes diversifying AI applications across vocational sectors, fostering cross-border collaboration, and developing innovative themes around curricula, personalized learning, and simulation-based training. Despite limitations related to database and language scope, this study offers strategic directions for advancing AI in VE research and strengthening its contributions to global vocational education development.